PENGARUH KUALITAS BAHAN BAKU DAN PROSES PRODUKSI TERHADAP KUALITAS PRODUK PADA UD. TAHU ROSYDI PUSPAN MARON PROBOLINGGO - Herlin Herawati; Dewi Mulyani (UNEJ e-Proceeding)
This study aims to determine the effect of Quality of Raw Materials and Production Processes on the Quality Products at UD Know Rosydi Puspan Maron Probolinggo. The population in this study is the number of consumers UD Know Rosydi Puspan Maron Probolinggo many as 31 people. While the method of data collections are observations, interviews, questionnaires, documentation, and literature studies. This research uses a quantitative approach manifold associative. Methods of data analysis using multiple linear regression. The results showed that all independent variables (quality of materials baku dan production processes) have significant influence on the quality of the product at UD. Rosydi know Puspan Maron Probolinggo. The influence of the quality of raw materials and production process of the variation (up and down) variable Y (quality products) amounted to 82.6%, while the remaining sebesar 17, 4% comes from factors other than the quality of materials and production processes tub.